A randomised prospective trial of intra‐operative oesophageal Doppler‐guided fluid administration in major gynaecological surgery. (30th September 2013) - McKenny, M.; Conroy, P.; Wong, A.; Farren, M.; Gleeson, N.; Walsh, C.; O'Malley, C.; Dowd, N.
Summary Intra‐operative oesophageal Doppler monitor‐guided fluid management has been associated with improved postoperative length of hospital stay and morbidity in gastrointestinal and orthopaedic surgery. We designed a randomised controlled trial to test the hypothesis that this approach to intra‐operative fluid management in major elective open gynaecological surgery would shorten the length of postoperative stay, defined as time to readiness for hospital discharge. Postoperative morbidity was evaluated as a secondary outcome. The oesophageal Doppler monitor group underwent intra‐operative fluid management using an oesophageal Doppler‐guided stroke volume optimisation algorithm. Control group (conventional fluid therapy) intra‐operative fluid management was based on conventional haemodynamic indices. In a single centre, 102 patients were randomly assigned: 51 to the oesophageal Doppler monitor group (51 analysed) and 51 to the control group (50 analysed). Evaluators who were blinded to patient assignment collected postoperative outcome data. There was no difference in the length of postoperative hospital stay between the groups: median (IQR [range]) number of days until ready for discharge was 6 (5–8 [4–25]) days in the oesophageal Doppler monitor group compared with 7 (5–9 [4–42]) days in the control group, p = 0.5. There was no difference between the groups in postoperative morbidity survey scores on postoperative days 1, 3 or 5. Seven patients in the oesophageal Doppler monitor group and 11 in the control group experienced postoperative complications (p = 0.41). These findings question whether intra‐operative oesophageal Doppler‐guided fluid therapy is of benefit in patients undergoing open gynaecological surgery.